Diagnostic accuracy of cone beam computed tomography used for assessment of apical periodontitis: an ex vivo histopathological study on human cadavers. (25th October 2018) - Kruse, C.; Spin‐Neto, R.; Evar Kraft, D. C.; Væth, M.; Kirkevang, L.‐L.
Abstract: Aim: To assess the diagnostic accuracy of Cone Beam Computed Tomography (CBCT) to diagnose apical periodontitis (AP) using histopathology of ex vivo human jaws as the reference standard. Methodology: Based on periapical radiographs of jaw specimens from human bodies donated for science, a sample of 223 teeth with 340 roots including all tooth groups, and different disease and treatment statuses was selected. Cone Beam Computed Tomography was performed using Cranex ® 3Dx (Soredex Oy, Tuusula, Finland), small field‐of‐view (5 × 5 cm), and isotropic resolution 0.085 mm. Three observers assessed the presence of AP using a probability index. Histopathological examination of the periapical area was used as a reference standard to calculate estimates of diagnostic accuracy. Results: For non‐root filled teeth all estimates of diagnostic accuracy; sensitivity (SENS), specificity (SPEC), positive predictive value (PPV) and negative predictive value (NPV) were high. All estimates were lower for root filled teeth. When mild AP was classified as 'AP', SENS, SPEC and NPV were significantly lower in root filled roots ( P  < 0.001 in all cases). The same tendency was seen when mild AP was classified as 'No AP' but here only the difference in SPEC was significant ( P  < 0.001). Conclusion: The diagnostic accuracy of CBCT used for diagnosis of AP is dependent on the treatment status of the tooth. For non‐root filled teeth the diagnostic accuracy of CBCT is high and almost all cases of AP can be diagnosed correctly with only a very small risk of over‐diagnosis. All diagnostic accuracy parameters were lower for root filled roots, hence the diagnosis of AP on root filled roots using CBCT was less accurate.